Penerapan Teknik Super Enkripsi Untuk Keamanan File Teks Menggunakan Gabungan Algoritma Beaufort Cipher dan Algoritma RSA - Yusuf Ramadhan Nasution; Abdul Halim Hasugian; M Mahyudi (LPPM STIKOM Tunas Bangsa, 2023)
Cryptography is an alternative solution that can be applied to protect and increase data security. This research will implement a combination of the Beaufort Cipher symmetric cryptographic algorithm and the RSA asymmetric cryptographic algorithm in a super encryption scheme to increase data security in text files. The combination of the two cryptographic algorithms is done by first encrypting the message contained in the text file using the Beaufort Cipher algorithm key, then re-encrypting it with the public key of the RSA algorithm to create an encrypted text file. The combination method between the two algorithms aims to obtain superior encryption (ciphertext) results so that they are not easy to crack, and also to handle the use of a single ciphertext which is comparatively weak because it only uses one cryptographic algorithm. This research produces a web-based application that can be used to secure text files using a combination of the Beaufort Cipher algorithm and the RSA algorithm in the super encryption technique.